SERUM URIC ACID - PHOSPHATE RATIO AS A DIFFERENTIAL DIAGNOSTIC MARKER OF PROSTATE DISORDERS - SUDHA K,; RESHMA K,; AKSHATHA L N, (International Journal of Pharma and Bio Sciences, 2014)
Prostate cancer (PC), benign prostatic hyperplasia (BPH) and prostatitis are the most common disorders of the prostate gland. Prostate specific antigen (PSA), the marker of prostate cancer has shown reasonable sensitivity but has limited specificity for distinguishing PC from BPH.This study attempts to evaluate the use of uric acid phosphate ratio as a tool in differential diagnosis of prostate disorders. PSA, uric acid and phosphate were estimated in serum of 75 patients with prostate disorders .PSA levels were significantly high in PC compared to other disorders. Phosphate levels were significantly lower in prostatitis patients, and an apparent increase in uric acid levels in BPH patients. Serum uric acid phosphate ratio was markedly high in prostatitis followed by BPH patients and least in PC establishing the role of the ratio in the differential diagnosis of prostate disorders.